2000
DOI: 10.1007/bf03343689
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical carcinoma manifesting pure primary aldosteronism: A case report and analysis of steroidogenic enzymes

Abstract: Adrenocortical carcinoma manifesting pure hyperaldosteronism is extremely rare. We report here a 61-year-old woman with biochemically proven primary aldosteronism due to right adrenocortical carcinoma. Computed tomographic scan showed 4.5x5.3 cm lobulated mass with tiny calcification, while there was no significant uptake of 131I-iodomethyl norcholesterol in the tumor. Immunohistochemical analysis demonstrated expression of steroidogenic enzymes in the tumor tissue: P-450scc, P-45c21, 3beta-hydroxysteroid dehy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The most common clinical syndrome associated with a functional adrenocortical carcinoma was Cushing’s syndrome, as reported in literature [1, 2, 3]. However, aldosterone-producing adrenocortical carcinoma is rare [4, 5, 8, 9]. Our case presented with hyperaldosteronism.…”
Section: Discussionmentioning
confidence: 61%
“…The most common clinical syndrome associated with a functional adrenocortical carcinoma was Cushing’s syndrome, as reported in literature [1, 2, 3]. However, aldosterone-producing adrenocortical carcinoma is rare [4, 5, 8, 9]. Our case presented with hyperaldosteronism.…”
Section: Discussionmentioning
confidence: 61%
“…Most patients have clinical manifestations such as Cushing syndrome (50%), virilism (30%) or feminization (12%). However, primary aldosteronism is rarely seen in patients with adrenocortical carcinoma [1]. Sasano et al [2] reported a case of adrenocortical carcinoma with primary aldosteronism expressing all the enzymes required for the biosynthesis of cortisol.…”
Section: Commentmentioning
confidence: 99%